Electrical distribution system Golar Hilli FLNG tanker vessel conversion project in Russia - Sino-ag, Ibar B. (Manila Professional Regulation Commission, 2015)
The GOLAR FLNG Conversion involves the conversion of an existing LNG carrier into a floating unit for gas liquefaction (hereinafter referred to a FLNG). The FLNG shall receive feed gas from an external source, and shall contain the necessary equipment for cleaning, pretreatment, liquefaction of the gas and boil-off gas handling. Furthermore LNG shall be stored onboard and offloaded to trading LNG carriers. The FLNG shall be designed for operation in non-specific sites. Design life is 20 years. The vessel shall be able to stay on location for up to 15 years without dry-docking and with minimal downtime for planned or unplanned maintenance. Thus it shall be developed with equipment and system designs that are robust, reliable, proven and possible to maintain in situ.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-667G donated by Mr. Jaime E. Mendoza.
Keywords: Electric power distribution